Endobronchial ultrasound-guided transbronchial incision and drainage in the treatment of mediastinal abscess - Huang, Zan-Sheng; Xiang, Qing; Wu, Xian-Li; Zhang, An-Mei; Liu, Shuang-Lin; Wang, Jing; Herth, Felix; Fan, Ye (Respiration, 2022)
Mediastinal abscess, mostly resulting from esophageal perforation or cardiothoracic surgery, is a serious condition carrying high morbidity and mortality. Antibiotic therapy alone normally did not achieve a satisfactory outcome, due to poor circulation of abscess that hampers drug delivery. Surgical intervention for debridement and drainage is recommended, but it poses a high risk in patients with poor health status and could lead to various complications. Recent studies proposed endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) as an effective alternative to surgery; however, repeated TBNA procedures are usually needed for complete clearance of the lesion, thus causing increased patient suffering and medical expenses. Here, we present the first case of successful application of EBUS-guided transbronchial incision and drainage, which provides a novel, safe, and effective treatment for patient with mediastinal abscess unwilling or unsuitable to undergo surgical intervention.
Gesehen am 30.01.2023